Prevalence of malnutrition among Samoan children aged 5 to 11 years in 2019-2020 - Courtney C. Choy; Vaimoana Filipo Lupematasila; Maria Siulepa Arorae; Faatali Tafunaina; Folla Unasa; Christina Soti-Ulberg; Muagututia S. Reupena; Rachel L. Duckham; Kima Faasalele-Savusa; Take Naseri; Nicola L. Hawley (Taylor & Francis Group, 2023)
Background Globally, rapid economic development, urbanisation, and nutrition transitions have led to rising levels of malnutrition in all forms. Aim The study objective was to document the prevalence of overweight/obesity, underweight, stunting, and anaemia among Samoan children in 2019-2020. Subjects and methods Children from the Ola Tuputupua'e "Growing Up" in Samoa study at ages 5-11 years with complete physical assessments were included. Overweight/obesity, underweight, and stunting were classified using World Health Organisation Z-scores for body mass index-for-age (BMIZ> +1), weight-for-age (WAZ< −2SD), and height-for-age (HAZ< −2SD), respectively. Anaemia was defined as haemoglobin concentration <11.5 g/dL. Prevalence was compared by child age, sex, and census region of residence (representing urbanicity and exposure to nutrition transition) using Wilcoxon two-sample, Chi-square, or Fisher's exact tests. Results The prevalence of overweight/obesity, underweight, stunting, and anaemia was 36.2%, 0.5%, 1.6%, and 31.6%, respectively. Overweight/obesity in children was positively associated with age and highly prevalent in periurban and urban regions. While children living in the rural region with the lowest exposure to nutrition transition had the highest prevalence of mild-to-moderate stunting, anaemia prevalence was lower compared to those in the urban region. No sex differences in malnutrition were observed. Conclusion Moderate-to-high levels of overweight/obesity and anaemia call for comprehensive intervention strategies.